2006
DOI: 10.1007/s10654-005-6030-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Web-based Questionnaires in Large Population-based Epidemiological Studies

Abstract: To date, few large web-based epidemiological studies have been performed in a population-based setting. Sweden has optimal prerequisites for web-based studies with more than 80% of the general population having access to the Internet. Our aim was to investigate (I) response rates in an epidemiological study using primarily the web as a tool for data collection and (II) whether socio-demographic patterns vary between responders to a web and a paper questionnaire. In 2003, we invited 47,859 women to complete a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
156
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(163 citation statements)
references
References 18 publications
3
156
2
2
Order By: Relevance
“…Nevertheless, there are still some barriers to online self-completion which could produce low response rates and selection bias. Although the reported participation rate varied a lot across online surveys [35,38,39], the 53.7% in our study is similar to those by other authors comparing between different modes of data collection, such as 64.2% and 53.3% participation rates reported by Kongsved [35] and Hohwu [40] studies. Remarkably, both studies showed a slightly better response rate with the paper mode: 73.2% versus 64,2% [35] and 56,2% versus 53,4% [40].…”
Section: Comparison Of Online Participation Rate With Prior Worksupporting
confidence: 87%
“…Nevertheless, there are still some barriers to online self-completion which could produce low response rates and selection bias. Although the reported participation rate varied a lot across online surveys [35,38,39], the 53.7% in our study is similar to those by other authors comparing between different modes of data collection, such as 64.2% and 53.3% participation rates reported by Kongsved [35] and Hohwu [40] studies. Remarkably, both studies showed a slightly better response rate with the paper mode: 73.2% versus 64,2% [35] and 56,2% versus 53,4% [40].…”
Section: Comparison Of Online Participation Rate With Prior Worksupporting
confidence: 87%
“…Although online data collection may not solve traditional problems faced for reaching the population sample [22], several studies argue in favor of high acceptability and feasibility of web-based questionnaires [23][24][25]. Moreover, the latter, particularly usable for analytical studies that focus on associations between variables [26], have major advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Bullying in the Australian medical workforce Australian Health Review bullying within the broad-based multi-domain questionnaire makes response bias by victims of bullying highly unlikely. Past web-driven population surveys have also generally yielded low to moderate response rates, 26 although the deleterious effect of the resulting biases has been argued. 27 As with all screening measures that use a sensitive rather than specific measure, we are at risk of including false positives amongst our positive cases.…”
mentioning
confidence: 99%